Keynes in action truth and expediency in public policy - Clarke, Peter 1942- (Cambridge University Press, 2023)
John Maynard Keynes died in 1946 but his ideas and his example remain relevant today. In this distinctive new account, Peter Clarke shows how Keynes's own career was not simply that of an academic economist, nor that of a modern policy advisor. Though rightly credited for reshaping economic theory, Keynes's influence was more broadly based and is assessed here in a rounded historical, political and cultural context. Peter Clarke re-examines the full trajectory of Keynes's public career from his role in Paris over the Versailles Treaty to Bretton Woods. He reveals how Keynes's insights as an economic theorist were rooted in his wider intellectual and cultural milieu including Bloomsbury and his friendship with Virginia Woolf as well as his involvement in government business. Keynes in Action uncovers a much more pragmatic Keynes whose concept of 'truth' needs to be interpreted in tension with an acknowledgement of 'expediency' in implementing public policy